2019
DOI: 10.1109/access.2019.2909812
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Social Capital on Knowledge Management Maturity of Nonprofit Organizations – Predictive Modelling Based on a Multilevel Analysis

Abstract: Nonprofit, nongovernmental organizations (NGOs) are important development actors that operate in ecosystems of multi and cross-sector stakeholders in order to reach the most vulnerable social groups of people. Having this in mind, our goal was to explore to what extent their social capital influences their knowledge in order to propose a model that could optimize their knowledge management maturity through social resources embedded into their structure. Therefore, we focused on NGOs from the European Union and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 52 publications
0
7
0
1
Order By: Relevance
“…Other scholars use multilevel algorithm models to predict the impact on the knowledge management level of nonprofit organizations (Mikovic et al, 2019). These scholars' research methods are highly comprehensive (Mikovic et al, 2019;Tai et al, 2020;Ma et al, 2021b), which is highly consistent with the research ideological objectives. Based on previous research ideas, this work proposes multicharacteristic variable optimization, uses a variety of algorithm models to warn the loss of telecom customers, and compares the prediction results of a variety of algorithm models.…”
Section: Related Researchmentioning
confidence: 98%
See 1 more Smart Citation
“…Other scholars use multilevel algorithm models to predict the impact on the knowledge management level of nonprofit organizations (Mikovic et al, 2019). These scholars' research methods are highly comprehensive (Mikovic et al, 2019;Tai et al, 2020;Ma et al, 2021b), which is highly consistent with the research ideological objectives. Based on previous research ideas, this work proposes multicharacteristic variable optimization, uses a variety of algorithm models to warn the loss of telecom customers, and compares the prediction results of a variety of algorithm models.…”
Section: Related Researchmentioning
confidence: 98%
“…Some scholars specifically include control variable analysis for large-scale multiobjective optimization problems (Ma et al, 2021b), Some scholars summarize multidisciplinary writing styles and then predict author identification (Tai et al, 2020). Other scholars use multilevel algorithm models to predict the impact on the knowledge management level of nonprofit organizations (Mikovic et al, 2019). These scholars' research methods are highly comprehensive (Mikovic et al, 2019;Tai et al, 2020;Ma et al, 2021b), which is highly consistent with the research ideological objectives.…”
Section: Related Researchmentioning
confidence: 99%
“…Furthermore, the role of 'people' or social factors has secured attention in the literature associated with knowledge management (van Dijk et al, 2016). This includes studies on the influence of social capital on knowledge management maturity of non-profit organisations (Miković et al, 2019) and research on the relationship between knowledge management and social capital with organisational health in educational hospitals (Aryankhesal et al, 2020). Furthermore, research studies have highlighted that ineffective collaboration and communication among employees can be a key impediment to knowledge management initiatives in organisations (Edwards et al, 2005) and a potential solution to this situation is the adoption of social media technologies to facilitate improved communication and joint working (Nisar et al, 2019).…”
Section: Inefficient Knowledge Managementmentioning
confidence: 99%
“…This empirical study indicated a significant positive relationship between KM strategy and KM practices. The research (Mikovic et al , 2019) deals with integrating social capital knowledge and influence into the KM system. The authors have designed knowledge-centric connected health-care (KCCH) (Li et al , 2019) in which a person-centric approach for knowledge creation was used.…”
Section: Health-care Knowledge Management Systemmentioning
confidence: 99%